Ownership structure and tax avoidance in Vietnam’s listed securities firms: The moderating role of foreign directors, firm leverage, and the COVID-19 pandemic - Nguyen, Thi Lam Anh; Le, Thi Bich Ngan (Asian Journal of Economic Modelling, 2025)
The purpose of this study is to investigate the connection between foreign ownership and tax avoidance among Vietnamese listed securities firms. It does this by focusing on the role of various other factors. This study uses data from 35 listed securities firms in Vietnam over a nine-year period (2015-2023). The Feasible Generalized Least Squares (FGLS) method is employed to estimate the impact of ownership structure on tax avoidance practices. The study reveals that foreign ownership plays a significant role in shaping tax avoidance practices, with greater foreign ownership leading to more aggressive tax planning strategies. We also discover that having a foreign director on boards has a stronger moderating effect, while firm leverage has a weaker moderating effect. The COVID-19 pandemic does not play a significant moderating role in the relationship between ownership structure and tax avoidance. The findings have important implications for policymakers, regulators, securities firms, and investors in Vietnam’s securities market. They highlight the need for enhanced monitoring and regulation of firms with significant foreign ownership and foreign directors on board to ensure tax compliance. The results can inform investment decisions and corporate governance practices in the context of ownership structures and tax strategies.